2016
DOI: 10.1186/s12879-016-1886-3
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of the importance of enteric fever as a cause of non-malarial febrile illness in patients admitted to Chittagong Medical College Hospital, Bangladesh

Abstract: BackgroundFever is a common cause of hospital admission in Bangladesh but causative agents, other than malaria, are not routinely investigated. Enteric fever is thought to be common.MethodsAdults and children admitted to Chittagong Medical College Hospital with a temperature of ≥38.0 °C were investigated using a blood smear for malaria, a blood culture, real-time PCR to detect Salmonella Typhi, S. Paratyphi A and other pathogens in blood and CSF and an NS1 antigen dengue ELISA.ResultsWe enrolled 300 febrile pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 35 publications
1
18
1
Order By: Relevance
“…In general, our study finds that a large percentage of infectious diseases in Dhaka can be attributed to enteric fever, consistent with single-center studies previously conducted in Bangladesh [ 14 , 17 ]. For instance, one study collected blood specimens from 103679 hospitalized and nonhospitalized patients attending the hospital attached to icddrb, between January 2005 and December 2014, and found that 13.6% of cultured blood samples were positive, with Salmonella Typhi being the most frequently isolated microorganism (36.9% of positive blood samples) [ 14 ].…”
Section: Discussionsupporting
confidence: 92%
“…In general, our study finds that a large percentage of infectious diseases in Dhaka can be attributed to enteric fever, consistent with single-center studies previously conducted in Bangladesh [ 14 , 17 ]. For instance, one study collected blood specimens from 103679 hospitalized and nonhospitalized patients attending the hospital attached to icddrb, between January 2005 and December 2014, and found that 13.6% of cultured blood samples were positive, with Salmonella Typhi being the most frequently isolated microorganism (36.9% of positive blood samples) [ 14 ].…”
Section: Discussionsupporting
confidence: 92%
“…Based on bacteriological evidence, the prevalence of typhoid fever in this study was 14.1%. Previous studies have reported comparable prevalence data of 11.3% to 18.7% among febrile patients26–28. In one previous study, Maude et al26 reported that 11.3% of a group of 300 febrile adults/children in Bangladesh were positive for typhoid, as determined by blood culture and polymerase chain reaction (PCR) for S. typhi.…”
Section: Discussionmentioning
confidence: 69%
“…Similar epidemiologic trends, in which ADE associated with multiple circulating serotypes has been considered a significant factor, have been observed in other regions such as in Indonesia and Brazil [ 22 , 23 ]. Circulation of DENV-1 was also documented during 2014–2016 in several countries neighboring Nepal including India, China, Pakistan, Bangladesh and Sri Lanka [ 24 28 ].…”
Section: Main Textmentioning
confidence: 99%